ADVERTISING ETHICS IN TELEVISION ACCORDING TO ISLAMIC VIEW - Faza, Ahmad Dzawil (IJIBE (International Journal of Islamic Business Ethics), 2022)
In business activities, advertising is a force that companies can use to attract as many consumers as possible. Advertising is an integral part of today's modern business activities because advertising plays a very important role in conveying information or messages about a product to the public. Almost every day people are flooded with advertisements presented by television. As a result, it is as if life in society in meeting daily needs is conditioned by advertising. However, there are not a few advertisements that have content and visualizations that are considered as duping and defrauding consumers, which is very far from the ethical values and morality of Islamic business. Moral and ethical problems in advertising arise when advertisements lose their normative values and only become propaganda for profit. Likewise, several companies that carry out advertising activities on television media that researchers observed contained content that was not in line with Islamic business ethics such as fraud, false promises to display women's genitals, giving the impression of being excessive, and so on. The type of this research is descriptive qualitative research with data collection techniques using observation and analysis of information from television, online media, and scientific journals. The data source used is secondary data. The results of this study inform that advertisements carried out by several companies on television such as beauty products, energy drinks, e-commerce, and snacks that are not in accordance with Islamic ethical behavior so that in the future there is a need for notification and warning from KPI or other advertising supervisory agencies.